OT education in Europe. A European master of science programme in occupational therapy. - Runge U; Fitinghoff H; Josephsson S; Kinébanian A; Sadlo G; Winding K (British Journal of Therapy & Rehabilitation, 2000)
This article summarizes the experiences of the working group involved in setting up the European Master of Science in occupational therapy. This process has taken place over the last 5 years, and the course currently involves 17 students from 5 countries. The first students will graduate in September 2001.